Mechanical properties and water-aging resistance of glass ionomer cements reinforced with 3-aminopropyltriethoxysilane treated basalt fibers. (April 2021) - Bao, Xiaozhen; Liu, Fang; He, Jingwei
Abstract: In order to improve interfacial adhesion between basalt fibers (BF) and glass ionomer cement (GIC) matrix, a silane named 3-aminopropyltriethoxysilane (APS) was used to modify the surface of BF. APS treated BF (APS-BF) was characterized by Fourier transform infrared spectroscopy (FT-IR), X-ray photoelectron spectroscopy (XPS), and scanning electron microscopy (SEM). The influence of APS concentration on mechanical properties of APS-BF reinforced GIC (APS-BF-GIC) was investigated, and water aging resistance of optimum APS-BF-GIC was also studied. The results showed that 5 wt% of APS was the optimum concentration for BF modification, for 5%APS-BF-GIC had the best comprehensive mechanical properties in all of APS-BF-GICs. Though 5%APS-BF-GIC had higher water sorption than BF-GIC and GIC, it still had higher flexural strength and exhibited better water-aging resistance.